DIFFERENCES IN EARLY CHILDHOOD LITERACY SKILLS BASED ON POSITIVE AND NEGATIVE PARENTING STYLES - Mite, Maria Stefania Bule; Laksana, Dek Ngurah Laba; Nafsia, Andi; Oka, Gde Putu Arya (STKIP Citra Bakti, 2026)
This study aims to describe the differences in literacy skills of early childhood children based on positive and negative parenting patterns at Harapan Bangsa Kindergarten in Bajawa. Literacy skills were assessed through three aspects: language comprehension, language expression, and literacy. The study used a comparative quantitative approach with a cross-sectional design. Data were obtained from 50 children through a parenting questionnaire filled out by parents, then respondents were categorized into positive parenting patterns (n = 32) and negative parenting patterns (n = 18). Analysis of differences was conducted using the nonparametric Mann–Whitney U test. The results showed a significant difference in literacy skills between the two groups (p < 0.05) with a large effect size, where children who received positive parenting patterns had higher literacy skills than children who received negative parenting patterns. Significant differences were also consistent in the three aspects of literacy, namely language comprehension, language expression, and literacy. These findings emphasize the importance of strengthening positive parenting patterns and home–school collaboration in creating an environment that supports language and literacy stimulation from an early age. This study is limited by its cross-sectional design and self-reported parenting measurements, which prevent direct causal conclusions. This study provides an original contextual contribution to early childhood education units in the Bajawa region, providing a comprehensive analysis of three aspects of literacy simultaneously, a topic that has been limited in previous research.